Effect of four neuraminidase inhibitors on influenza in Osaka, Japan: An eight‐year survey. (31st October 2019) - Tochino, Yoshihiro; Yoshii, Naoko; Fujioka, Masashi; Hamazaki, Takashi; Kawaguchi, Tomoya; Kakeya, Hiroshi; Shuto, Taichi
Abstract: Background: After the A/H1N1 influenza pandemic in 2009, two new drugs against influenza, namely laninamivir and peramivir, were released in 2010 in Japan. We investigated prescription trends of four neuraminidase inhibitors (NAIs), which are laninamivir, peramivir, oseltamivir, and zanamivir, and assessed clinical data related to influenza for 8 years. Methods: Patients living in Osaka Prefecture and diagnosed with influenza responded to a postcard questionnaire that collected data regarding their demographic characteristics, symptoms including fever, prescribed drugs, and influenza type. Results: Laninamivir was most prescribed to patients aged ≥ 10 years, and oseltamivir was most prescribed to patients aged < 10 years. All four NAIs had similar effects on influenza. Patients with type A influenza experienced fever alleviation earlier than those with type B influenza. Older patients tended to have lower fever. Most seasons had similar results. Conclusions: Our descriptive epidemiologic study revealed the status of patients with influenza and their medication use. Abstract : We showed the data of eight seasons and report prescription trends of four neuraminidase inhibitors (NAIs) and time course of fever in patients after taking these inhibitors. Doctors, especially general physicians, should consider how to choose anti‐influenza drugs. This study based on our 8‐year survey should be helpful to them when deciding which NAIs should be chosen in clinical settings and for which patients.